‘Bergendang’ and Its Spatial Use in Traditional Sarawak Malay House - Yon Syafni, Samat; Syed Ahmad Iskandar, Syed Ariffin; Nurakmal, Abdullah@ Goh Tuo Ho; John Hwa Seng, Ting (2023)
Bergendang is a uniquely Sarawak Malay traditional entertainment frequently held during social gatherings at home. This paper investigates the spatial use of bergendang activity in traditional Malay houses along the Sarawak River in Kuching. The research employed a qualitative case study design approach through field study observation and semi-structured interviews. Findings revealed different spatial use of bergendang for early and later model of Sarawak Malay houses, which is also associated with social status of house owners. Spatial study on traditional Malay houses in other parts of Sarawak is recommended for constructing northern Borneo region's vernacular Malay house framework.